PENYULUHAN TENTANG ISPA PADA MASYARAKAT DESA BOBO KAB. HALMAHERA BARAT - Andriani, Tanti Nova; Diman, Tiara; Aulia, Rifanda; Lestari, Tutik (MAJU : Indonesian Journal of Community Empowerment, 2025)
Acute Respiratory Tract Infection is a health problem, especially in toddlers. ARI attacks babies, children, adults and the elderly. ARI can be treated independently or by consulting a doctor. The activity was carried out on Friday, May 2, 2025 in Bobo Village RT 01 involving 15 mothers of toddlers. This activity aims to increase mothers' knowledge about ARI through health education. The methods used include pretest and posttest to measure changes in knowledge, lectures, and discussions. There was an increase in knowledge of the average pretest value (11.8) and posttest (13.67). This shows that health education is effective in increasing mothers' knowledge about.